2015
DOI: 10.1088/0960-1317/25/12/125009
|View full text |Cite
|
Sign up to set email alerts
|

Fluid transport via pneumatically actuated waves on a ciliated wall

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Similarly, in [11,13], it is stated that the coordinated beating of cilia is particularity effective at maintaining a more directed surface propulsion. It has been also shown that the propulsive effect of a system of pneumatically controlled flexible oscillators is strongly affected by their phase relationships [44]. Accordingly, we suggest that the metachronal coordination of a system of individual oscillators can result in collective propulsion if the oscillators are brought together in a sufficientlyviscous environment.…”
Section: Introductionmentioning
confidence: 61%
“…Similarly, in [11,13], it is stated that the coordinated beating of cilia is particularity effective at maintaining a more directed surface propulsion. It has been also shown that the propulsive effect of a system of pneumatically controlled flexible oscillators is strongly affected by their phase relationships [44]. Accordingly, we suggest that the metachronal coordination of a system of individual oscillators can result in collective propulsion if the oscillators are brought together in a sufficientlyviscous environment.…”
Section: Introductionmentioning
confidence: 61%
“…They experimentally proved the concept by employing their ciliabased micromixer to improve bioreaction efficiency of a biotin-avidin assay and a DNA hybridization assay [92]. Pressure-induced actuation of cilia with pneumatically actuated waves underneath a ciliated wall [93] and with pneumatic pipes directly integrated into the cilia [94] have recently been reported. In the latter case the cilia-like actuators have relatively large dimensions, 1 mm diameter and 8 mm length, but the fluid speeds measured reached correspondingly large values in the order of 19 mm/s.…”
Section: Microstructures Based On Pdmsmentioning
confidence: 99%
“…The vast majority of artificial cilia consist of microactuators that are incorporated in silicone rubber pillars or plate‐like flexible structures in order to mimic the biological hair‐like design. Current actuation methods include electric fields, magnetic fields, vibrations, mechanical forces, or pressurized fluids . However, asymmetric motion remains the most challenging feature to mimic in artificial cilia systems.…”
Section: Introductionmentioning
confidence: 99%